A posture prediction method for ergonomic assessment of user-product interactions while grasping using musculoskeletal human models - Hartmann, Carla; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
Using digital human models (DHMs) as the virtual representation of the human body enables the integration of ergonomic assessments in the product design process. Especially the use of DHMs in the early phases of product design can be decisive for competitive factors such as ergonomics or usability. Therefore, we present a method for automatic posture generation for grasping tasks using a musculoskeletal human model. This method enables ergonomic analyses without ergonomic knowledge of the product designer or subject tests. We implemented the presented method for a cylinder grasping scenario using the open source software OpenSim. Subsequently, we evaluated the implementation by means of a parameter stud
Keywords: Posture prediction; musculoskeletal simulation; digital human model

Approaching an ergonomic future: An affordance-based interaction concept for digital human models - Wolf, Alexander; Krüger, Daniel; Miehling, Jörg; Wartzack, Sandro (Procedia CIRP Volume 84, 2019)
Digital human models offer great potential for the evaluation of physical human factors throughout all phases of product development. Unfortunately, digital human models lack a generic user-product interaction model to use them as universal and truly predictive CAE tools. In this contribution, we propose a concept for a generic and integrated interaction model based on the concept of affordances, the technology of CAD features and posture- and movement-prediction methods. Furthermore, we propose an affordance taxonomy, which shall enable a universal methodical description of interactions occurring during product us
Keywords: user-centered design; user-product interaction; digital human models; affordances; CAD features; human factors

Auslegung von amorphen Kohlenstoffschichten für Knie-Totalendoprothesen - Wartzack, Sandro; Rothammer, Benedict; Marian, Max; Wolf, Alexander; Miehling, Jörg; Tremmel, Stephan (WiGeP News, 2019)

Biomechanical Digital Human Models: Chances and Challenges to Expand Ergonomic Evaluation - Peters, Markus; Quadrat, Eric; Nolte, Alexander; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro; Leidholdt, Wolfgang; Bauer, Sebastian; Fritzsche, Lars; Wischniewski, Sascha; et al. (Human Systems Engineering and Design, 2018)
Nowadays, ergonomic evaluation of work can be done using Digital Human Models (DHM). One advantage is to reduce the need for corrective measures by supporting a more prospective ergonomic work design. Although ergonomic models provide useful information for risk assessment, single working tasks with minor changes in work place design are difficult to evaluate. Instead, biomechanical models can analyze single movements or body postures, taking internal forces in muscles and joints into account. Therefore, the main goal of this work is to establish an interface between a biomechanical human model (AnyBody) and the “Editor for manual work activities” (ema) to enrich ergonomic evaluation with biomechanical parameters. First results demonstrate that the automatically generated movements of ema showed some specific deviations relative to the subjects’ movements in experimental conditions. Optimization of kinematic data in AnyBody is necessary to ensure more physiological movements which are highly valuable for ergonomic evaluatio
Keywords: Human factors; Digital Human Models; Ergonomics; Biomechanics; Anthropometry; Risk assessment

Bridging the sim2real gap. Investigating deviations between experimental motion measurements and musculoskeletal simulation results—a systematic review - Wechsler, Iris; Wolf, Alexander; Shanbhag, Julian; Leyendecker, Sigrid; Eskofier, Björn; Koelewijn, Anne; Wartzack, Sandro; Miehling, Jörg (Frontiers in Bioengineering and Biotechnology, 2024)

Challenges in interaction modelling with digital human models – A systematic literature review of interaction modelling approaches - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Ergonomics, 2020)
Digital human models (DHM) allow for a proactive ergonomic assessment of products by applying different models describing the user-product interaction. In engineering design, DHM tools are currently not established as computer-aided ergonomics tools, since (among other reasons) the interaction models are either cumbersome to use, unstandardised, time-demanding or not trustworthy. To understand the challenges in interaction modelling, we conducted a systematic literature review with the aim of identification, classification and examination of existing interaction models. A schematic user–product interaction model for DHM is proposed, abstracting existing models and unifying the corresponding terminology. Additionally, nine general approaches to proactive interaction modelling were identified by classifying the reviewed interaction models. The approaches are discussed regarding their scope, limitations, strength and weaknesses. Ultimately, the literature review revealed that prevalent interaction models cannot be considered unconditionally suitable for engineering design since none of them offer a satisfactory combination of genuine proactivity and universal validity
Keywords: Computer-aided ergonomics; digital human models; interaction modelling; engineering design; posture and movement prediction

Computer Aided Ergonomics: Evaluation Study of a Interaction Model for Digital Human Models - Wolf, Alexander; Fackler, Konrad; Reulbach, Magnus; Wartzack, Sandro; Miehling, Jörg (Proceedings of the Design Society, 2022)
In user-centred design, digital human models hold the potential for proactive evaluations of ergonomics or discomfort in terms of a computer aided ergonomics tool. Therefore, models predicting human interaction behaviour, are necessary. In this contribution we present such a model as well as its initial evaluation. The evaluation is performed by applying the interaction model to a specific use case, conducting a comparison with an empirical subject study. The evaluation shows that similar and realistic human behaviour was predicted, which was consistent in terms of whole-body strai
Keywords: user-centred design; interaction design; digital human models; evaluation; computer-aided ergonomics

Einsatz von Rousseau Modellen für die Vorhersage menschlicher Bewegung zur muskuloskelettalen Simulation im AnyBody Modeling System - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (7. CADFEM medical conference, 2017)
Biomechanische Simulationsmethoden ermöglichen die Analyse und Bewertung von Bewegungen und Kräften des menschlichen Bewegungsapparates. Dadurch wird es möglich Fragestellungen bezüglich ergonomischer/ biomechanischer Parameter in frühen Planungsphasen zu beantworten und diese entsprechend in die Planung einfließen zu lassen. So lässt sich beispielsweise ein Arbeitsablauf bereits bei der Planung nach ergonomischen Gesichtspunkten ausrichten, oder ein Produkt schon in den frühen Entwicklungs- und Konstruktionsabschnitten nach nutzerspezifischen Kriterien gestalten. Dennoch sind biomechanische Simulationsmethoden im industriellen Umfeld bei weitem nicht so verbreitet, wie herkömmliche Simulationsmethoden der Mehrkörpersimulation, oder der Strukturmechanik. Dies liegt insbesondere daran, dass für jedes neu erstellte biomechanische Modell neue Messungen stattfinden müssen, damit dieses berechnet werden kann. Für den weitläufig genutzten Ansatz der inversen Dynamik werden als Eingangsdaten die Bewegung und die externen Kräfte benötigt, welche klassischerweise in Bewegungsanalyselaboren erfasst werden müssen. Unter deren Angabe können die Muskelkräfte und die Beanspruchung der Gelenke berechnet werden. Gegenwärtig erscheint dieser Aufwand gegenüber dem Nutzen allerdings als nicht gerechtfertigt. Der Nutzen der biomechanischen Simulationsmethoden steht indes außer Frage. Deshalb gilt es den zu betreibenden Aufwand zu reduzieren. Dies kann durch Modelle geschehen, die eine Vorhersage der üblicherweise zu messenden Eingangsdaten ermöglichen. Die Vorhersage der äußeren Kräfte lässt sich im Rahmen des Optimierungsproblems der inversen Dynamik durchführen. Die Vorhersage der Bewegung kann mittels der Verwendung von Rousseau Modellen gelingen. Diese zwingen einem muskuloskelettalen Menschmodell gewisse Zwangsbedingungen auf, welche gemäß der zu erzeugenden Bewegung unterschiedlich gewichtet werden. Durch dieses Aufzwingen, von sich teilweise wiedersprechenden Zwangsbedingungen, wird das muskuloskelettale Menschmodell zu einem kinematisch überbestimmten Fall. Mithilfe eines Optimierungsverfahrens lässt sich der bestmögliche Kompromiss zur Erfüllung der Zwangsbedingungen finden, wodurch wiederum die Vorhersage einer nachvollziehbaren Bewegung möglich wird. Diese Vorgehensweise wird anhand eines konkreten Anwendungsfalles unter Zuhilfenahme des AnyBody Modeling System vorgestellt.

Elementary affordances: A study on physical user-product interactions - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Procedia CIRP 91, 2020)
Digital human models enable a pro-active and virtual assessment of ergonomics in design. Despite this huge potential, possibilities of user-product interaction modelling, in terms of postures or movement generation, are limited and poorly integrated in common virtual design tools. To address this deficiency, we propose the concept of “elementary affordances”. These universally describe parts of human interaction behavior and shall serve as a modelling interface for posture and movement prediction algorithms. This paper presents an empirical study, identifying 18 elementary affordances, proving that parts of human interaction behavior can be described via a relatively small set of elementary affordances.<br
Keywords: design for ergonomics; human centered design; user centred design; user-product interaction; digital human models; affordances; human factors; computer aided engineering; virtual engineering; computer aided design

Enhancing Dynamic Consistency of Multimodal Motion Data in Musculoskeletal Simulation - Wechsler, Iris; Wolf, Alexander; Wartzack, Sandro; Miehling, Jörg (27th Congress of the European Society of Biomechanics, 2022)
Introduction Digital human models can be used to determine biomechanical parameters (e.g. muscle or joint reaction forces) virtually and in a non-invasive way [1]. Hereby, subject-specific models lead to more reliable simulation results in this context [2]. Moreover, even though current sensor and measuring systems can achieve high-quality data, the measurements are still error-prone and subject to uncertainties such as noise or jumps. Furthermore, kinematic and dynamic inconsistencies between the measured data and the motion capabilities of the human body can occur. We assume that motion tracking accuracy and consistency will be increased when multimodal data, e.g., some combination of position, orientation, EMG, or surface data, is considered. Therefore, our goal is to research and develop methods for filtering and analysing multimodal motion measurement data in conjunction with individualized digital human models. In this paper we want to discuss available approaches. Methods Subject-specific individualization of the applied musculoskeletal human models in multiple domains (anthropometry, mobility, strength) is to be achieved through a combination of subject-specific manual measurements and population data [3]. Further, we aim to develop a method for kinematically consistent and precise motion tracking. The standard method, Inverse Kinematics, minimises the difference between measured and virtual marker and coordinate positions in a least squares approach to compute generalized coordinate trajectories [4]. The novel tracking algorithm should include different types of data, which are weighted in relation to each other. This way the observed movement information from different data sources should be transferred to the digital model in order to get the most accurate and consistent simulation results possible. Nevertheless, the problem regarding the dynamic consistencies between the motion of the model and the measurements still remains. For this we also want to investigate methods to enhance dynamic consistency and further develop a dynamic tracking method that is able to generate kinematically and also dynamically consistent motion data. Therefore, dynamic components (e.g. muscle activation, accelerations) are to be included in the tracking method. Results There are various approaches available in literature for enhancing dynamic consistency (cf. figure 1). The EMG-informed forward simulation approach, for example, tracks measured marker trajectories while replicating EMG measurements to obtain dynamic consistency [5-7]. Controller-based solution approaches optimise measured trajectories through forward simulation with a time-limited observation interval to enhance dynamic consistency [8]. Also, trajectory optimization using direct collocation and a Kalman filter have already been used to achieve dynamically consistent movement simulations [9,10]. Discussion In the next step, a systematic literature review will be conducted based on the mentioned results, in order to identify and analyse all relevant dynamic tracking solutions regarding multimodal motion data. Main focus will be the classification into different solution approaches. Moreover, input and output variables, the used model and the regarded dynamic component will be explored. Based on these results the solution approach for our application of multimodal motion data is to be set up. This new musculoskeletal simulation approach is then to be evaluated regarding accuracy and usability and to be benchmarked against the standard methods of biomechanical motion capture and analysis. References 1. Seth et al, Computational Biol, 14(7), 2018. 2. Lund et al, Internat Biomech, 2:1-11, 2015. 3. Miehling, Comput Methods Biomech Biomed Engin, 22(15):1209-1218, 2019. 4. Delp et al, IEEE Trans Biomed Eng, 54: 1940-1950, 2007. 5. Sartori et al, PLoS One, 7(12), 2012. 6. Bailly et al, Front Bioeng Biotechnol, 2021. 7. Moissenet et, Front. Neurorobot, 2019. 8. Thelen et al, J Biomech, 39:1107-1115, 2006. 9. Dembia et al, PLoS Comput Biol, 16(12), 2020. 10. Bonnet et al, J Biomech, 62:140-147, 2017. Acknowledgements This work was (partly) supported by the Deutsche Forschungs-gemeinschaft (DFG, German Research Foundation) under Grant SFB 1483–Project-ID 442419336. <br

Evaluation of Active Shoulder Exoskeleton Support to Deduce Application-Oriented Optimization Potentials for Overhead Work - Sänger, Johannes; Yao, Zhejun; Schubert, Tim; Wolf, Alexander; Molz, Carla; Miehling, Jörg; Wartzack, Sandro; Gwosch, Thomas; Matthiesen, Sven; Weidner, Robert (Applied Sciences, 2022)
Repetitive overhead work with a heavy load increases the risk for work-related shoulder disorders. Occupational exoskeletons supporting arm elevation are potential solutions to reduce that risk by lowering the physical strains on the shoulder. Many studies have reported a reduction in shoulder stress in various overhead tasks by using such exoskeletons. However, the support demand can vary in each phase of motion as well as in each individual task. This paper presents a laboratory study with five participants to evaluate the influence of the support level of an active shoulder exoskeleton in different motion phases (e.g., arm lifting, screw-in, and arm lowering of two overhead tasks) to identify the potential optimization of support at each phase. Results show that the support level of the exoskeleton should be adapted to the motion phase of the two chosen tasks. A higher support force is desired for the screw phase compared to the arm lifting and lowering phases, and the support level needs to be reduced immediately for arm lowering after the screw phase. The time for switching the support levels can be recognized by the electric current of the screwdrive
Keywords: human–machine interaction; biomechanical analysis; sEMG; interaction forces; user experience; power tool; exoskeleton

Femoral Shape and Size Variability from segmented CT datasets for patient-specific THA planning - Fleischmann, Christopher; Leher, Irina; Sesselmann, Stefan; Scherb, David; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Current Directions in Biomedical Engineering, 2020)
Biomechanical functionality of artificial hips strongly correlates with quality of life of patients after total hip arthroplasty. As the numbers of total hip arthroplasty are growing due to increasing life expectancy, biomechanical research is of utmost importance to improve the implants used and the operative procedures applied. Multibody simulation is used to predict forces and moments inside the human body. Generic scaling is usually performed to adapt the human models used in multibody simulation to individual patients. However, since the shape and size of the bones can vary considerably, this type of scaling often is not sufficient. In this work various CT datasets were used to quantify differences of individual femoral shapes, especially with regard to important biomechanical hip parameters, such as the CCD angle or the femoral offset. Our results prove that multibody simulations should be modeled more patientspecific to be able to calculate articular forces and moments more precisely, and thus, to improve surgical planning.

Method for Using IMU-Based Experimental Motion Data in BVH Format for Musculoskeletal Simulations via OpenSim - Wechsler, Iris; Wolf, Alexander; Fleischmann, Sophie; Waibel, Julian; Molz, Carla; Scherb, David; Shanbhag, Julian; Franz, Michael; Wartzack, Sandro; Miehling, Jörg (Sensors, 2023)
Biomechanical simulation allows for in silico estimations of biomechanical parameters such as muscle, joint and ligament forces. Experimental kinematic measurements are a prerequisite for musculoskeletal simulations using the inverse kinematics approach. Marker-based optical motion capture systems are frequently used to collect this motion data. As an alternative, IMU-based motion capture systems can be used. These systems allow flexible motion collection without nearly any restriction regarding the environment. However, one limitation with these systems is that there is no universal way to transfer IMU data from arbitrary full-body IMU measurement systems into musculoskeletal simulation software such as OpenSim. Thus, the objective of this study was to enable the transfer of collected motion data, stored as a BVH file, to OpenSim 4.4 to visualize and analyse the motion using musculoskeletal models. By using the concept of virtual markers, the motion saved in the BVH file is transferred to a musculoskeletal model. An experimental study with three participants was conducted to verify our method’s performance. Results show that the present method is capable of (1) transferring body dimensions saved in the BVH file to a generic musculoskeletal model and (2) correctly transferring the motion data saved in the BVH file to a musculoskeletal model in OpenSim 4.4.<br
Keywords: biomechanics; musculoskeletal modelling and simulation; inertial sensors; motion tracking; data transfer

Methods for integrating postural control into biomechanical human simulations: a systematic review - Shanbhag, Julian; Wolf, Alexander; Wechsler, Iris; Fleischmann, Sophie; Winkler, Jürgen; Leyendecker, Sigrid; Eskofier, Björn; Koelewijn, Anne; Wartzack, Sandro; Miehling, Jörg (Journal of neuroEngineering and rehabilitation, 2023)
Understanding of the human body’s internal processes to maintain balance is fundamental to simulate postural control behaviour. The body uses multiple sensory systems’ information to obtain a reliable estimate about the current body state. This information is used to control the reactive behaviour to maintain balance. To predict a certain motion behaviour with knowledge of the muscle forces, forward dynamic simulations of biomechanical human models can be utilized. We aim to use predictive postural control simulations to give therapy recommendations to patients suffering from postural disorders in the future. It is important to know which types of modelling approaches already exist to apply such predictive forward dynamic simulations. Current literature provides different models that aim to simulate human postural control. We conducted a systematic literature research to identify the different approaches of postural control models. The different approaches are discussed regarding their applied biomechanical models, sensory representation, sensory integration, and control methods in standing and gait simulations. We searched on Scopus, Web of Science and PubMed using a search string, scanned 1253 records, and found 102 studies to be eligible for inclusion. The included studies use different ways for sensory representation and integration, although underlying neural processes still remain unclear. We found that for postural control optimal control methods like linear quadratic regulators and model predictive control methods are used less, when models’ level of details is increasing, and nonlinearities become more important. Considering musculoskeletal models, reflex-based and PD controllers are mainly applied and show promising results, as they aim to create human-like motion behaviour considering physiological processes.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Biomechanical human model; Biomechanics; Forward dynamics; Musculoskeletal model; Postural control; Simulation; Systematic review

Musculoskeletal Simulation and Evaluation of Support System Designs - Miehling, Jörg; Wolf, Alexander; Wartzack, Sandro (Developing Support Technologies - Integrating Multiple Perspectives to Create Assistance that People Really Want, 2018)

Parametric Movement Synthesis: Towards virtual Optimisation of Man-Machine Interaction in Engineering Design - Wolf, Alexander; Wartzack, Sandro (Proceedings of the DESIGN 2018 15th International Design Conference, 2018)
A parametric movement synthesis approach is introduced, which allows the adaptation of a synthesized movement to a specific use case by varying geometrical parameters. This parametric movement synthesis empowers the product developer to optimize products purely virtually in terms of ergonomics and (dis-)comfort by using musculoskeletal simulation. We developed such a parametric model for a lifting movement to analyse several scenarios. The results of the analyses show to what extent this procedure may support the product developer to improve the man-machine interaction of products.<br
Keywords: human centred design; musculoskeletal simulation; movement synthesis; ergonomics; design for x (DfX)

Patientenspezifische Modellierung des passiven Bewegungsapparates als Grundlage für die präoperative Abschätzung postoperativer Folgeerscheinungen des endoprothetischen Hüftgelenkersatzes - Scherb, David; Kurz, Marlene; Fleischmann, Christopher; Wolf, Alexander; Sesselmann, Stefan; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
During preoperative planning of total hip arthroplasty, the patients’ biomechanics is widely reduced to geometrical parameters. To provide the orthopedist more functional biomechanical parameters, a method is shown to model a patient-specific musculoskeletal human model via CT-/MRI-images in OpenSim. Main focus of this contribution is the setup of the passive musculoskeletal system. A generic human model and a segmented dataset of bones from the hip area serve as the basis for the modelling process. During the method the generic model is processed by scaling it to the anthropometry of the patient and adjusting subject-specific kinematics and shapes gathered from the segmented data. Finally, to reach the patient-specific representation the segmented bones are integrated into the mode
Keywords: Patient-specific modeling; Image-based model; Musculoskeletal human model; OpenSim; Total Hip Arthroplasty

Prädiktive biomechanische Simulation am Beispiel von ergonomischer Produktoptimierung in Burkina Faso / Predictive biomechanical simulation based on the example of ergonomic product optimization in Burkina Faso - Meißner, Ruth; Wolf, Alexander; Wartzack, Sandro; Miehling, Jörg (Konstruktion, 2022)
In der Produktentwicklung gewinnen nutzerzentrierte Designprozesse zunehmend an Bedeutung. Muskuloskelettale Simulationstools ermöglichen die Abbildung und Simulation des menschlichen Bewegungsapparats während der Nutzer-Produkt-Interaktion auf Basis experimentell erhobener Bewegungsdaten. Durch prädiktive Methoden der Bewegungserzeugung soll der Aufwand der experimentellen Bewegungserfassung reduziert und eine proaktive sowie virtuelle Analyse von Produktergonomie und Gebrauchstauglichkeit ermöglicht werden. Dieser Beitrag präsentiert eine solche prädiktive Methode zur Abbildung der Nutzer-Produkt-Interaktion. Diese wurde für die Designoptimierung eines Trikes für Menschen mit Behinderungen in Burkina Faso entwickelt. In product development, the impact of user-centered design processes is growing rapidly. Biomechanical simulation enables the realistic representation of the human musculoskeletal system during user-product interactions based on experimentally captured motion data. Using predictive methods for motion generation, the effort for experimental motion capture can be reduced enabling a proactive and virtual analysis of product ergonomics and usability. This paper presents such a predictive method for modelling user-product interaction. This was developed for the design optimisation of a tricycle for persons with disabilities in Burkina Fas

Proactive Integration of User Data into Engineering Processes - A Generic Approach and Specific Examples - Wolf, Alexander; Buker, Tina; Molz, Carla; Scherb, David; Wartzack, Sandro; Miehling, Jörg (Human-Automation Interaction. Manufacturing, Services and User Experience, 2022)
User-centered design (UCD) describes an approach, which aims to increase customer satisfaction, comfort, usability, user experience, aesthetics and perceived quality by enhancing the fit between products and their users in the respective context of use. To achieve this goal, a multitude of different methods can be applied. All these methods integrate the user into the design process, in order to evaluate and improve the user-product interaction. This integration can be achieved via two different approaches. The classical approach on the one hand, integrates the user personally, e.g. focus groups, user tests, interviews or surveys. The proactive approach on the other hand, integrates the user in form of a user model, which is universally applicable for one aspect of user-product interaction, e.g. digital human models for the evaluation of physiological comfort and ergonomics or generic high-level guidelines for enhancing positive product emotions. The proactive approach is of great interest for industrial and engineering design, as it offers time- and cost-efficient user integration especially in the early, predominantly virtual phases of product design. This chapter takes a closer look at the proactive approach and presents four specific examples concerning computer aided ergonomics, assistive device design, preoperative evaluation of implants and product-related user stigma.
Keywords: User-centered design; User-product interaction; Proactive user integration

Roadmap to Consider Physiological and Psychological Aspects of User-product Interactions in Virtual Product Engineering - Wartzack, Sandro; Schröppel, Tina; Wolf, Alexander; Miehling, Jörg (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
To successfully facilitate user-centred design, a multitude of different aspects has to be considered, from purely physiological to psychological-emotional factors. The overall aim is to increase the customer satisfaction by enhancing the fit between products and their users in the respective context of use. Further virtualisation of user-centred design processes holds the potential to convey the concepts of frontloading and predictive engineering from classical product engineering. Our vision is to facilitate a comprehensive consideration of user-product interactions in virtual product engineering operationalised by the mission to develop methods and tools to assess and design user-product interactions according to physiological and psychological aspects. A variety of work has already been done to model musculoskeletal user groups, to configure, predict, simulate and optimise physical user-product interactions, to integrate such models into CAD or to map individual subjective values to product design. Nevertheless, there are still research areas to be addressed to enable a comprehensive implementation of the mentioned approach. These are discussed in the present contribution
Keywords: User centred design; Simulation; Integrated product development; Affective Engineering; Biomechanical digital human models

Segmentation of musculotendinous structures of the hip from 3d imaging for patient-specific individualization of biomechanical simulations - Fleischmann, Christopher; Scherb, David; Leher, Irina; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro; Sesselmann, Stefan (Advances in Intelligent Systems and Computing, 2021)
Due to a steady increase of total hip arthroplasty, biomechanical multibody simulations are moving more and more into focus. These simulations allow to calculate forces, moments and muscle activities in the human body and, thus, can help to improve surgery planning and outcomes. However, generic human body models based on anthropometric data are mostly used for these simulations. Since these models are not customized to patients, there is a need to adapt the models to the individual patient. Therefore, 3D models of bones are created by segmentation of CT and MRI scans and assigned different landmarks. This allows to define both, the shape and size of bones, in this case the femur, which leads to patient-specific adjustments of muscle attachment points. Also muscles can be segmented to determine important parameters such as muscle volume, allowing the definition of important simulation parameters, like the maximum isometric force or the tendon slack length of individual patients leading to customized models.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Biomechanics; Multibody simulation; Muscle function; Muscle segmentation; Orthopaedics; Subject-specific modeling and simulation; Surgery planning; Total hip arthroplasty

Simplifying Computer Aided Ergonomics: A User-Product Interaction-Modeling Framework in CAD Based on a Taxonomy of Elementary Affordances - Wolf, Alexander; Wagner, Yvonne; Oßwald, Marius; Miehling, Jörg; Wartzack, Sandro (IISE Transactions on Occupational Ergonomics and Human Factors, 2021)
OCCUPATIONAL APPLICATIONS
CRIS-Team WoS Importer:2021-07-09

Simplifying Ergonomic Assessment for Designers: A User-Product Interaction-Modelling Framework in CAD - Wolf, Alexander; Wagner, Yvonne; Oßwald, Marius; Miehling, Jörg; Wartzack, Sandro; Wolf, Alexander; Wagner, Yvonne; Oßwald, Marius; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 21st Congress of the International Ergonomics Association (IEA 2021), 2021)
Digital human models have not yet reached their full potential for proactive virtual assessment of ergonomics in engineering and industrial design. Especially the modelling of interaction between user and product often is time demanding, cumbersome, unstandardized and embedded insufficiently in the computer-aided engineering environment. On the one hand, the interaction modelling needs to be applicable for a majority of products and shall contain as much a-priori knowledge regarding human behavior as possible. On the other hand, the method needs to be appropriate for designers, without special ergonomic expertise or human behavior training. In this contribution, we present an interaction-modelling framework based on the concept of affordances, which ought to resolve these partly contradictable demands. Hence, 31 elementary affordances, describing fundamental physical interaction possibilities between human end effectors and rudimental (product) geometries, were deduced using a classification method. The elementary affordances shall serve as a medium for interaction modeling. For this purpose, we introduce an interaction modelling routine, implemented in a CAD system, which makes use of the identified elementary affordances in terms of CAD-features. Those enable designers to apply interaction possibilities directly to a CAD-model in order to define the constraints for a DHM simulatio
CRIS-Team Scopus Importer:2021-08-13
Keywords: User product interaction; Digital human models; Affordance; CAD; Interaction modelling

Subject-specific tribo-contact conditions in total knee replacements: a simulation framework across scales - Rothammer, Benedict; Wolf, Alexander; Winkler, Andreas; Schulte-Hubbert, Felix; Bartz, Marcel; Wartzack, Sandro; Miehling, Jörg; Marian, Max (Biomechanics and Modeling in Mechanobiology, 2023)
Fundamental knowledge about in vivo kinematics and contact conditions at the articulating interfaces of total knee replacements are essential for predicting and optimizing their behavior and durability. However, the prevailing motions and contact stresses in total knee replacements cannot be precisely determined using conventional in vivo measurement methods. In silico modeling, in turn, allows for a prediction of the loads, velocities, deformations, stress, and lubrication conditions across the scales during gait. Within the scope of this paper, we therefore combine musculoskeletal modeling with tribo-contact modeling. In the first step, we compute contact forces and sliding velocities by means of inverse dynamics approach and force-dependent kinematic solver based upon experimental gait data, revealing contact forces during healthy/physiological gait of young subjects. In a second step, the derived data are employed as input data for an elastohydrodynamic model based upon the finite element method full-system approach taking into account elastic deformation, the synovial fluid’s hydrodynamics as well as mixed lubrication to predict and discuss the subject-specific pressure and lubrication condition
Keywords: Total knee replacement; Biomechanics; Biotribology; Multiscale simulation; In silico modeling

Towards Virtual Assessment of Human Factors: A Concept for Data-Driven Prediction and Analysis of Physical User-product Interactions - Wolf, Alexander; Binder, Nicole; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
The early consideration of human factors in product development hugely favours the development of products, which excel with a positive user experience. The virtual environment of product development however, still has significant gaps in the virtual assessment and simulation of human factors, especially for user-product interactions composed of human movements. This motivates us to introduce a concept for data-driven prediction and analysis of user-product interactions. Heart of the concept is a predictive component that models the interaction between the user, represented by a musculoskeletal model, and the product, represented by product characteristics. We describe the implementation of this concept based on a pilot study for a lifting task. Motion capturing was performed to build a database and compare the results of our novel approach. The resulting kinematic and dynamic quantities show similar curve profiles with a small constant offset to the measured data. This indicates that the concept enables the virtual comparison of different designs or concepts regarding human factor
Keywords: User centred design; Simulation; Early design phases; User-product interaction; Data-driven movement prediction

Virtual planning and evaluation of human work Virtuelles Planen und Bewerten menschlicher Arbeit - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro; Quadrat, Eric; Nolte, Alexander; Fritzsche, Lars; Bauer, Sebastian; Spitzhirn, Michael; Peters, Markus; Leidholdt, Wolfgang; Wischniewski, Sascha (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
CRIS-Team Scopus Importer:2024-12-16

Virtuelles Planen und Bewerten menschlicher Arbeit - Wolf, Alexander; Miehling, Jörg; Quadrat, Eric; Nolte, Alexander; Fritzsche, Lars; Bauer, Sebastian; Spitzhirn, Michael; Peters, Markus; Leidholdt, Wolfgang; Wischniewski, Sascha; Wartzack, Sandro (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
Die ergonomische Gestaltung von Arbeitsplätzen ist eine Grundvoraussetzung zur Vorbeugung von Erkrankungen des Muskel-Skelett-Systems durch körperliche Arbeit. In diesem Beitrag wird das Forschungs- und Entwicklungsprojekt „ema2AnyBody“ vorgestellt, in dem ein Softwaretool zur virtuellen Planung und Bewertung menschlicher Arbeit entwickelt wird. Das Besondere dabei: Die Bewertung kann anhand biomechanischer Beanspruchungsgrößen erfolgen, die mithilfe einer automatisierten biomechanischen Simulation erhoben werde

Vorgehensweisen zur Vorhersage menschlicher Bewegung durch muskuloskelettale Simulation - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
Musculoskeletal simulations are holding the capability to quantify man-machine interactions of systems which are not build yet. Thus, they have the capability to be an important CAE-tool in product development. The most common approach of musculoskeletal simulations is the inverse dynamic analysis. Unfortunately this approach has view disadvantages, which are the main reason why musculoskeletal simulations are not in broad application yet. The main disadvantage is that measurements have to take place for every simulation. To overcome the measurements for inverse dynamics, movement and external forces have to be predicted. We present two approaches for motion prediction and describe which of them is more suitable to match the needs of product development.
Keywords: musculoskeletal simulation; posture- and movement-prediction; human centered design; man–machine interaction